SURFACE STRATEGY TAXONOMY: GRAMMATICAL ERRORS ANALYSIS IN THE THIRD-SEMESTER STUDENTS’ DESCRIPTIVE ESSAY - Annafi’in Nur Rixha; Idrus Alhamid; Siti Rokhmah; Syamsir Bin Ukka (Fakultas Tarbiyah IAIN Fattahul Muluk Papua, 2021)
English and Indonesian are grammatically different. The difference proves that the rules and the application of grammar are the difficult problems in writing English. Based on previous preliminary research, many Third-Semester students of English Education Study Program had problems using grammar. This is supported by the results of unstructured interviews by researcher against students. Then students made mistakes they cannot correct called errors. As English Education students, they must have good competence in all language skills to become a good English teacher. In the future, students will teach writing effectively if they master the grammatical understanding.This research’s objectives were to find: (1) The the types of grammatical errors based on surface strategy taxonomy found in students’ descriptive essay,(2) The dominant grammatical error based on surface strategy taxonomy found in students’ descriptive essay,(3) The factors causing students made grammatical error in writing descriptive essays.To achieve the objectives, a qualitative method is used. Data collected by observation, interview and documentation from students’ descriptive essay worksheet then analyzed using error analysis.The findings of the research: (1) Grammatical errors are Misformation (3rd Person Singular, Plural, Auxiliary Verb, Dictionaries, Preposition, Conjunction, Pronoun, Singular, Simple Present Tense, Simple Past Tense), Omission (Simple Present Tense, Agreement, Auxiliary Verb, Plural, Article, Pronoun, Conjunction, Preposition, Adverb), Addition (Simple Additions, Double Marking), Misordering (Adjective, Pronoun, Auxiliary Verb). (2) The dominant grammatical error is Misformation with 47.05% from 170 errors. (3) The factors causing error are Interlingual and Intralingual.